1997
DOI: 10.1577/1548-8667(1997)009<0279:nasovh>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

North American Strain of Viral Hemorrhagic Septicemia Virus is Highly Pathogenic for Laboratory-Reared Pacific Herring

Abstract: Specific-pathogen-free Pacific herring Clupea pallasi were reared in the laboratory from eggs and then challenged at 5, 9, and 13 months of age by waterborne exposure to low (101.5-2 .5 plaque-forming units [PFU] per milliliter), medium (103.5-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 6 publications
6
83
0
Order By: Relevance
“…In addition to acute manifestations of VHS in Pacific herring which are well-documented (Kocan et al 1997, Hershberger et al 2006, 2007, 2010a, we found that the disease can also manifest in this species as a chronic form that is characterized by viral persistence within infected hosts for extended periods with nearbackground levels of VHS-specific host mortality (Fig. 1, Table 1).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition to acute manifestations of VHS in Pacific herring which are well-documented (Kocan et al 1997, Hershberger et al 2006, 2007, 2010a, we found that the disease can also manifest in this species as a chronic form that is characterized by viral persistence within infected hosts for extended periods with nearbackground levels of VHS-specific host mortality (Fig. 1, Table 1).…”
Section: Discussionsupporting
confidence: 57%
“…Once exposed, laboratory stocks of Pacific herring typically experience acute disease followed by rapid mortality (Kocan et al 1997), and epizootics in the wild are likely initiated as a result of a combination of environmental stressors and concentration or amplification mechanisms associated with viral shedding from infected individuals within a school (Hershberger et al 2010a). Individuals that survive these epizootics become refractory to disease, indicating the involvement of a protective adaptive immune response (Kocan et al 2001, Hershberger et al 2007, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…6) to concentrations capable of producing lethal infections among juvenile laboratory-reared, spec~fic pathogen-free herring (Kocan et al 1997). The lower concentrations in water samples collected from outside Pounds #1998-5 and #1998-6 may have resulted from samples being taken on the upstream slde of slight currents circulating through the pounds during tide changes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 16 organisms that occurred in Pacific herring Clupea pallasii at >10% prevalence (Table 1), only Ichthyophonus hoferi and VHSV met all 4 criteria for significance at the population level (Kocan et al 1997, Marty et al 2003. VHSV occurred sporadically in fish sampled in the spring, but it was never cultured in any of the 710 fish sampled in the fall (Table 1).…”
Section: Significant Lesions and Pathogensmentioning
confidence: 99%